The Impact of Audit Committee Characteristics on Earnings Management: Evidence in Chinese Listed Companies - ZHANG, Wenxin (2020)
This research examines the effectiveness of the audit committee’s characteristics in restraining earnings management. Taking the agency theory and the positive accounting theory as the theoretical framework, this study makes the hypotheses that the characteristics of the audit committee would have significant impacts on earnings management. To evaluate the perspective, this research adopts 160 eligible listed companies found in the Shanghai Stock Exchange 180 Index of China from 2016 to 2018. Discretionary accruals are calculated by using the Modified Jones Model to reflect the corporate earnings management. In addition, a panel data regression analysis is carried out by taking the discretionary accruals as the dependent variable, and the size, independence and meeting times of the audit committee as the independent variables. The study finds that the size of the audit committee of sample companies is positively related to the earnings management. Yet neither of the other two showed a significant relationship with discretionary accruals. This conclusion suggests that small-scaled audit committees may play a better role in controlling earnings management behaviours. Also, it could be inferred that listed companies in China pay more attention to the form rather than the essence of the audit committee, so the effectiveness of curbing earnings management is not obvious. The findings of this study play a positive role in the normative management of listed companies in China. Key words: Audit Committee, Earnings Management, China, Shanghai Stock Exchange, Agency Theory, Positive Accounting Theory, Modified Jones Model.